Twelve years and thirteen days : remembering Paul and Sheila Wellstone - Gydesen, Terry (University of Minnesota Press, 2003)
Essay by Jeff BlodgettSenator Paul Wellstone is remembered for his infectious enthusiasm and his ardent devotion to helping all people gain a voice in American politics. In a remarkable collection of more than seventy photographs, Twelve Years and Thirteen Days commemorates the Wellstones commitment to social and economic justice and will be an inspiration to those throughout the country who share their values.